2005
DOI: 10.1111/j.1365-2559.2005.02200.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 expression in different epithelial types in columnar lined oesophagus indicates varying levels of expanded and aberrant proliferative patterns

Abstract: These findings suggest that oxynto-cardiac mucosa occurs in a low damage environment and intestinal metaplasia in a high damage environment along the length of the columnar lined oesophageal segment. Aberrant proliferative patterns with Ki67 staining are not useful in differentiating reactive epithelia from low-grade dysplasia, but may prove useful in the diagnosis of high-grade dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 28 publications
(37 reference statements)
0
14
0
2
Order By: Relevance
“…Most interestingly, aberrant Ki67 expression was comparable in cardiac mucosa, intestinal metaplasia without dysplasia and low grade-dysplasia. Aberrant Ki67 expression was absent in oxyntic and oxyntocardiac mucosa [62]. Taken together, these data suggest that when compared to oxyntocardiac mucosa, cardiac mucosa may signify a switch towards "malignant" progression [38,62].…”
Section: Follow Up Of Clementioning
confidence: 80%
See 3 more Smart Citations
“…Most interestingly, aberrant Ki67 expression was comparable in cardiac mucosa, intestinal metaplasia without dysplasia and low grade-dysplasia. Aberrant Ki67 expression was absent in oxyntic and oxyntocardiac mucosa [62]. Taken together, these data suggest that when compared to oxyntocardiac mucosa, cardiac mucosa may signify a switch towards "malignant" progression [38,62].…”
Section: Follow Up Of Clementioning
confidence: 80%
“…In contrast to oxyntic mucosa, expanded Ki67 expression from the lower (= normal) towards the middle third of the foveolar pit was detected in different types of CLE, following a step wise increase from oxyntic, onxytocardiac and cardiac mucosa to intestinal metaplasia, low-, high-grade dysplasia and adenocarcinoma [62]. Frequency of aberrant Ki67 expression within surface and foveolar epithelium in cardiac mucosa showed a stepwise increase from cardiac mucosa and intestinal metaplasia towards low-, highgrade dysplasia and adenocarcinoma [62]. Most interestingly, aberrant Ki67 expression was comparable in cardiac mucosa, intestinal metaplasia without dysplasia and low grade-dysplasia.…”
Section: Follow Up Of Clementioning
confidence: 90%
See 2 more Smart Citations
“…However, they observed inconsistent results in indefinite for dysplasia samples. Olvera et al 26 found no value for Ki-67 immunohistochemical staining in distinguishing between low-grade dysplastic epithelium and cardiac mucosa or nondysplastic intestinal epithelium. Our study corroborates the results of the study by Hong et al, 25 except that we found lower mitotic counts in indefinite for dysplasia than in low-grade dysplasia.…”
Section: Discussionmentioning
confidence: 99%